Growth performance of the seabass Lates calcarifer (Blotch) in sea cage at Vizhinjam Bay along the south-west coast of India - Anil, M. K.; Santhosh, B.; Jasmine, S.; Saleela, K. N.; George, Rani Mary; Kingsly, H. Jose; Unnikrishnan, C.; Rao, G. Hanumanta; Rao, G. Syda (Indian Journal of Fisheries, 2011)
The growth potential of the Asian seabass, Lates calcarifer in floating sea cage was assessed by rearing them in a large HDPE floating cage moored at Vizhinjam Bay, south-west coast of India. Seabass seed (mean weight and mean total length, 2.5 g and 53 mm respectively) were nursery reared in hapas in December 2008, fed on pellet feed and grown to an average size of 28 g and 135 mm in 60 days, with a survival rate of 60%. Subsequently, the juveniles were stocked into the cages at a stocking rate of 60 nos. m-3 in February 2009, fed on trash fish and reared for a period of 112 days during which they grew to an average size of 540 g and 328 mm. Weight gain per day increased from 0.2 g in December 2008 to 7.71 g in May 2009, while SGR decreased from 5.88 to 2.47. The hydrological parameters viz., temperature, pH, salinity, dissolved oxygen and microbial load recorded were at optimal levels for the normal growth of seabass. The results obtained indicated that cage culture of seabass in the sea can provide significant advantages in terms of faster growth and effective utilisation of water volume.